“Yiddish literature for the masses”?: a reconsideration of who read what in jewish Eastern Europe - Quint, Alyssa Pia (AJS review, 2005)
In the early 1880s, the staunch Hebraist and bibliophile Ephraim Deinard (1846–1930) became a reluctant witness to the fast-paced growth of modern Yiddish culture that began in his hometown of Odessa. At the time, Deinard owned a Hebrew bookshop that had been sliding toward bankruptcy until he grudgingly adapted his wares to better reflect the market forces of the Jewish reading culture. In Memories of My People (Zikhronot bat עami), he briefly accounts for (in his view) the ill fortune of being forced to sell the Yiddish books that his customers demanded of him rather than the Hebrew literature he held so dear. Although he mentions a host of nineteenth-century Yiddish writers whom the reader will come to know in the following pages, for our present purpose, it is sufficient to remark upon the catalytic agency he assigns to the Yiddish romance novelist Nakhum Shaykevitsh (aka Shomer) (1849–1905) and Avraham Goldfaden (1840–1908), best known as the father of the Yiddish theatre. Deinard writes: [...]